Measuring embodiment: A review of methods for prosthetic devices - Segil, Jacob L.; Roldan, Leah Marie; Graczyk, Emily L. (Frontiers in Neurorobotics, 2022)
The development of neural interfaces to provide improved control and somatosensory feedback from prosthetic limbs has initiated a new ability to probe the various dimensions of embodiment. Scientists in the field of neuroprosthetics require dependable measures of ownership, body representation, and agency to quantify the sense of embodiment felt by patients for their prosthetic limbs. These measures are critical to perform generalizable experiments and compare the utility of the new technologies being developed. Here, we review outcome measures used in the literature to evaluate the senses of ownership, body-representation, and agency. We categorize these existing measures based on the fundamental psychometric property measured and whether it is a behavioral or physiological measure. We present arguments for the efficacy and pitfalls of each measure to guide better experimental designs and future outcome measure development. The purpose of this review is to aid prosthesis researchers and technology developers in understanding the concept of embodiment and selecting metrics to assess embodiment in their research. Advances in the ability to measure the embodiment of prosthetic devices have far-reaching implications in the improvement of prosthetic limbs as well as promoting a broader understanding of ourselves as embodied agents.